2019
DOI: 10.3233/jad-180923
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Amyloid-β Protein Precursor Processing Modulators Lower Amyloid-β Peptide Levels via cKit Signaling

Abstract: Alzheimer’s disease (AD) is characterized by the accumulation of neurotoxic amyloid-β (Aβ) peptides consisting of 39-43 amino acids, proteolytically derived fragments of the amyloid-β protein precursor (AβPP), and the accumulation of the hyperphosphorylated microtubule-associated protein tau. Inhibiting Aβ production may reduce neurodegeneration and cognitive dysfunction associated with AD. We have previously used an AβPP-firefly luciferase enzyme complementation assay to conduct a high throughput screen of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Treatment with SHP2 inhibitors or cKit inhibitors enhanced the phosphorylation of amyloid-β protein precursor, thereby reducing the accumulation of amyloid-β in neuronal cells. 76 SHP2 also interacted with tau protein to form an SHP2-tau complex in neuronal cells. The formation of this complex was associated with the activation of SHP2 and the phosphorylation of tau.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 99%
“…Treatment with SHP2 inhibitors or cKit inhibitors enhanced the phosphorylation of amyloid-β protein precursor, thereby reducing the accumulation of amyloid-β in neuronal cells. 76 SHP2 also interacted with tau protein to form an SHP2-tau complex in neuronal cells. The formation of this complex was associated with the activation of SHP2 and the phosphorylation of tau.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 99%
“…The prevalence of AD continues to grow because of the increase in the aging population (Hodson, 2018). As the major pathological marker of AD brain, amyloid β protein (Aβ), a polypeptide consisting of 39–43 acid residues, is proteolytically generated by cleavage of amyloid precursor protein (Chen et al, 2019). Aβ accumulation in and around the cerebral vasculature, known as cerebral amyloid angiopathy (CAA), has been found in more than 80% of AD patients (Kovari, Herrmann, Hof, & Bouras, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The gold treatment is cholinesterase inhibitors, which provide limited short-term cognitive benefits, whilst their clinical value remains a matter of controversy, considering the risk of side effects (Tricco et al, 2013;Hill et al, 2017). Indeed, the regulation of Amyloid-β protein precursor (AβPP) phosphorylation by small molecules is a novel therapeutic intervention for AD (Chen et al, 2019) . However, several studies have shown a reduction in Aβ load in the brain, but with the lack of beneficial effects on cognitive outcome measures, as well as impaired brain function (van der Kant, Goldstein, & Ossenkoppele, 2020).…”
Section: Introductionmentioning
confidence: 99%